2006
DOI: 10.1111/j.1570-8703.2006.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonanoic acid, other alkanoic acids, and related compounds as antifeedants in Hylobius abietis pine weevils

Abstract: A medium‐length, straight‐chain alkanoic acid, nonanoic acid, is known from laboratory microassays to be an antifeedant in adults of the large pine weevil, Hylobius abietis (L.) (Coleoptera: Curculionidae). Our hypothesis was that we could find new, less volatile alkanoic acids or related compounds suitable for field application and with improved long‐term duration. Alkanoic acids of varying chain lengths (C6–C13) were tested for antifeedant activity in H. abietis adults. Microassay choice tests showed that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Similar to our results, the compound exhibited antifeedant activity against the weevil when tested in a feeding bioassay (Borg-Karlson et al 2006). In accordance with the decreased antifeedant activity found for carboxylic acids with chains longer than C10 (Månsson et al 2006), no antifeedant activity was found for hexadecanoic-, linoleic-, or linolenic acids that were present in almost all extracts (Table 1).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Similar to our results, the compound exhibited antifeedant activity against the weevil when tested in a feeding bioassay (Borg-Karlson et al 2006). In accordance with the decreased antifeedant activity found for carboxylic acids with chains longer than C10 (Månsson et al 2006), no antifeedant activity was found for hexadecanoic-, linoleic-, or linolenic acids that were present in almost all extracts (Table 1).…”
Section: Discussionsupporting
confidence: 76%
“…We found only hexanoic acid in the pentane bark extracts of Ilex and Alnus, and nonanoic acid in the pentane bark extract of Ilex (Table 1). Thus, the feeding avoidance of H. abietis on the ten woody species investigated in this work is not fully explained by the presence of these carboxylic acids, as it was for linden (Månsson et al , 2006.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations